Microbially mediated barite dissolution in anoxic brines. (January 2017) - Ouyang, Bingjie; Akob, Denise M.; Dunlap, Darren; Renock, Devon
Abstract: Fluids injected into shale formations during hydraulic fracturing of black shale return with extraordinarily high total-dissolved-solids (TDS) and high concentrations of barium (Ba) and radium (Ra). Barite, BaSO4, has been implicated as a possible source of Ba as well as a problematic mineral scale that forms on internal well surfaces, often in close association with radiobarite, (Ba, Ra)SO4 . The dissolution of barite by abiotic processes is well quantified. However, the identification of microbial communities in flowback and produced water necessitates the need to understand barite dissolution in the presence of bacteria. Therefore, we evaluated the rates and mechanisms of abiotic and microbially-mediated barite dissolution under anoxic and hypersaline conditions in the laboratory. Barite dissolution experiments were conducted with bacterial enrichment cultures established from produced water from Marcellus Shale wells located in northcentral Pennsylvania. These cultures were dominated by anaerobic halophilic bacteria from the genus Halanaerobium . Dissolved Ba was determined by ICP-OES and barite surfaces were investigated by SEM and AFM. Our results reveal that: 1) higher amounts of barium (up to ∼5 × ) are released from barite in the presence of Halanaerobium cultures compared to brine controls after 30 days of reaction, 2) etch pits that develop on the barite (001) surface in the presence of Halanaerobium exhibit a morphology that is distinct from those that form during control experiments without bacteria, 3) etch pits that develop in the presence of Halanaerobium exhibit a morphology that is similar to the morphology of etch pits formed in the presence of strong organic chelators, EDTA and DTPA, and 4) experiments using dialysis membranes to separate barite from bacteria suggest that direct contact between the two is not required in order to promote dissolution. These results suggest that Halanaerobium increase the rate of barite dissolution in anoxic and high ionic strength solutions. Additionally, the increase in rate occurs without direct microbe-mineral contact suggesting that metabolites secreted by the bacteria may be responsible for promotion of dissolution. The findings of this study have implications for understanding barium cycling in marine/hypersaline environments, release of barium (and associated radium) from waste solids generated from energy and mining industries, as well as potential for developing new anti-scaling chemicals. Highlights: Higher amounts of barium are released from barite in the presence of Halanaerobium . Bacteria produce etch pits that are distinct from controls. Bacteria produced etch pits that are similar to those produced by strong chelators. Bacteria do not have to make direct contact to promote dissolution.